2009
DOI: 10.21273/hortsci.44.5.1425
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertigation Concentration and Timing of Application Affect Nitrogen Nutrition, Yield, Firmness, and Color of Apples Grown at High Density

Abstract: A randomized complete block, split-plot experiment with six replicates was established and maintained for the first six fruiting seasons (1999 to 2004) in a high-density apple [Malus sylvestris (L.) Mill var. domestica (Borkh.) Mansf.] orchard on M.9 rootstock planted in Apr. 1998. This report assesses responses to six main-plot fertigation treatments, each containing three tree subplots of five different cultivars (Ambrosia, Cameo, Fuji, Gala, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 25 publications
1
30
0
2
Order By: Relevance
“…Several studies have consistently reported the negative effects high N applications had on reducing red color or increasing the green background of apples (Marcelle, 1995;Neilsen et al, 2009;Tahir, Johansson, & Olsson, 2008) due to a decrease in both chlorophyll degradation and anthocyanin synthesis in the skin (Wang & Cheng, 2009). High N also reduced storage performance in apple (Fallahi, Fallahi, & Seyedbagheri, 2006) and kiwi fruits (Vizzotto, Lain, & Costa, 1999).…”
Section: Applied N and Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have consistently reported the negative effects high N applications had on reducing red color or increasing the green background of apples (Marcelle, 1995;Neilsen et al, 2009;Tahir, Johansson, & Olsson, 2008) due to a decrease in both chlorophyll degradation and anthocyanin synthesis in the skin (Wang & Cheng, 2009). High N also reduced storage performance in apple (Fallahi, Fallahi, & Seyedbagheri, 2006) and kiwi fruits (Vizzotto, Lain, & Costa, 1999).…”
Section: Applied N and Qualitymentioning
confidence: 99%
“…Leaching of N and phosphorous (P) due to excessive applications in agriculture are widely considered the main cause of eutrophication in fresh and salt water supplies throughout the world (Burt et al, 2009b;Erhart, Feichtinger, & Hart, 2007). Several practices have recently been implemented to try to reduce ground water pollution by N, such as split applications (Drake, Raese, & Smith, 2002), target timing (Tagliavini & Marangoni, 2002;Wade, Holzapfel, Degaris, Williams, & Keller, 2004), integrated production (Ganeshamurthy et al, 2004;Peck et al, 2006), fertigation (Neilsen, Neilsen, & Herbert, 2009;Raina, Thakur, Shashi, & Spehia, 2005), best management practices (Alva, Paramasivam, Fares, Obreza, & Schumann, 2006;, foliar applications (Dong, Neilsen, Neilsen, & Fuchigami, 2005;Reay, Fletcher, & Thomas 1998), and varying the type of N sources (El-Boray, Mostafa, Iraqi, & Mohamed, 2006;Erhart et al, 2007;Racskó et al, 2008;Rosen & Allan, 2007). While not all of the above mentioned practices reduced the total amount of N applied; all were effective in limiting pollution by increasing plant N use efficiency.…”
Section: Nitrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods of irrigation affect water consumption, which is a critical issue in many parts of the world including the Pacific Northwest region of the United States. Irrigation methods and injection of nutrients, particularly nitrogen, through water (fertigation) also play major roles in apple fruit quality and production (Fallahi et al, 2001a;Neilsen et al, 2009).…”
mentioning
confidence: 99%
“…N was fertigated daily as calcium nitrate (15.5N-0P-0K) for 6 weeks after bloom to provide 75 g N/tree. Subsequent research indicated that the N application rates were in excess of requirements for high-density apple, which can be as low as 25 g N/tree (Neilsen et al, 2009). P was fertigated for 1 d immediately after full bloom and before the start of regular N applications as ammonium polyphosphate (10N-15P-0K), which supplied 20 g P/tree and 13.3 g N/tree.…”
Section: Methodsmentioning
confidence: 99%